Stress-related biobehavioral responses, symptoms, and physical activity among female veterans in the community: An exploratory study. (December 2016) - Wang, Hsiao-Lan; Visovsky, Constance; Ji, Ming; Groer, Maureen
Abstract: Background: Female veterans experience multiple stresses during their lifetime. Some of them seek care in the civilian community. Common physical and psychological symptoms among female veterans include pain, fatigue, sleep quality, and depression. Physical activity has the potential to improve their well-being. Objectives: This study was guided by the concept of allostasis. The purpose of the study was to determine the associations among stress-related biobehavioral responses and symptoms as well as to determine if physical activity moderated these associations among female veterans. Design/Settings/Participants/Methods: A cross-sectional and exploratory design was implemented among 82 female veterans (46 ± 10.57 years old) at a community event. Self-reported questionnaires and blood and hair samples were collected. Descriptive statistics and multivariate analyses were applied in this secondary data analysis. Findings: Female veterans experienced moderate perceived stress and greater body mass index, C-reactive protein, and hair cortisol levels at the same time as they reported moderate levels of pain and fatigue, poor sleep quality, and considerable depressive symptoms. The findings showed that greater body mass index was significantly associated with more severe pain and poor sleep quality. Physical activity negatively moderated the relationship between perceived stress and pain. Conclusion: Female veterans need services to manage body weight and help them engage in physical activity. Nurse educators are responsible for instructing nurses to properly identify female veterans in the civilian community facility and to provide care in a respectful manner. Highlights: Female veterans in the community experience moderate perceived stress and physical/psychological symptoms. Proper weight management and physical activity consultation should be part of the care plan for female veterans. Nurse educators need to provide training in care for female veterans to nurses in the civilian community.